A Study of the Performance of a Cloud Datacenter Server - Mershad, Khaleel (2015)
In a previous work, we presented a system which combines active solid state drives and reconfigurable FPGAs (which we called reconfigurable active SSD nodes, or simply RASSD nodes) into a storage-compute node that can be used by a cloud data-center to achieve accelerated computations while running data intensive applications. To hide the complexity of accessing RASSD nodes from applications, we proposed in another work a middleware framework which handles all low-level interactions with the hardware. The Middleware Server (MWS), which manages a group of RASSD nodes, has the role of bridging the connection between a client and the nodes. In this paper, we present extensions to the MWS to enable it to operate within a collaborative cloud environment, and we develop a model to evaluate the performance of the collaborative MWS. This model represents a study of the utilization of three hardware resources of the MWS: CPU, memory, and network interface. For each, we derive the parameters that affect its operations, and propose formulas for its utilization. The results describe the capacity of a MWS, and hence can be used to decide on the number of MWSs in a collaborative cloud datacenter.